47.4k views
1 vote
Find the unique solution to the following linear system X = (0 -1 2 3)X + (e' -e')
X(0)=(5 4)

1 Answer

6 votes

It looks like the system is supposed to be


\mathbf x'=\begin{bmatrix}0&-1\\2&3\end{bmatrix}\mathbf x+\begin{bmatrix}e^t\\e^(-t)\end{bmatrix}

with the initial condition,
\mathbf x(0)=\begin{bmatrix}5&4\end{bmatrix}^\top.

Compute the eigensystem for the coefficient matrix:


\begin{vmatrix}-\lambda&-1\\2&3-\lambda\end{vmatrix}=\lambda^2-3\lambda+2=(\lambda-1)(\lambda-2)=0


\lambda_1=1\implies\begin{bmatrix}-1&-1\\2&2\end{vmatrix}\mathbf v_1=\mathbf 0\implies\mathbf v_1=\begin{bmatrix}1\\-1\end{bmatrix}


\lambda=2\implies\begin{bmatrix}-2&-2\\2&1\end{bmatrix}\mathbf v_2=\mathbf 0\implies\mathbf v_2=\begin{bmatrix}1\\-2\end{bmatrix}

So we have the characteristic solution,


\mathbf x_c=C_1e^(\lambda_1t)\mathbf v_1+C_2e^(\lambda_2t)\mathbf v_2


\mathbf x_c=C_1e^t\begin{bmatrix}1\\-1\end{bmatrix}+C_2e^(2t)\begin{bmatrix}1\\-2\end{bmatrix}

For the non-homogeneous part, we can guess a particular solution of the form


\mathbf x_p=te^t\begin{bmatrix}a\\b\end{bmatrix}

(We might have started with
e^t instead, but that is already accounted for in the first characteristic solution.)

Its derivative is


{\mathbf x_p}'=e^t\begin{bmatrix}a\\b\end{bmatrix}+te^t\begin{bmatrix}a\\b\end{bmatrix}=e^t\begin{bmatrix}at+a\\bt+b\end{bmatrix}

Substitute
\mathbf x_p into the system and solve for
a,b:


e^t\begin{bmatrix}at+a\\bt+b\end{bmatrix}=te^t\begin{bmatrix}0&-1\\2&3\end{bmatrix}\begin{bmatrix}a\\b\end{bmatrix}+e^t\begin{bmatrix}1\\-1\end{bmatrix}


\begin{bmatrix}at+a\\bt+b\end{bmatrix}=\begin{bmatrix}-bt+1\\(2a+3b)t-1\end{bmatrix}


\implies a=1,b=-1

and so the particular solution is


\mathbf x_p=te^t\begin{bmatrix}1\\-1\end{bmatrix}

The general solution to the system is then


\mathbf x=\mathbf x_c+\mathbf x_p


\mathbf x=C_1e^t\begin{bmatrix}1\\-1\end{bmatrix}+C_2e^(2t)\begin{bmatrix}1\\-2\end{bmatrix}+te^t\begin{bmatrix}1\\-1\end{bmatrix}

Use the given initial conditions to solve for the remaining coefficients.


\mathbf x(0)=\begin{bmatrix}5\\4\end{bmatrix}


\implies\begin{bmatrix}5\\4\end{bmatrix}=C_1\begin{bmatrix}1\\-1\end{bmatrix}+C_2\begin{bmatrix}1\\-2\end{bmatrix}


\implies C_1=14,C_2=-9

Then the solution to the initial value problem is


\mathbf x=14e^t\begin{bmatrix}1\\-1\end{bmatrix}-9e^(2t)\begin{bmatrix}1\\-2\end{bmatrix}+te^t\begin{bmatrix}1\\-1\end{bmatrix}


\mathbf x=\begin{bmatrix}14e^t-9e^(2t)+te^t\\-14e^t-18e^(2t)-te^t\end{bmatrix}

User Ali H
by
5.3k points